The Role of Social Media Marketing and Brand Image in Shaping Purchase Decisions through Purchase Intention - Maharani, Adilla Dwi; Murwanti, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: his study aims to analyse the influence of Social Media Marketing and Brand Image on Purchase Decisions, with Purchase Intention as a mediating variable, in the context of Cilok Umi Asih consumers in Nganjuk, East Java.Methodology: The research employed a quantitative approach using primary data collected through an online questionnaire distributed to consumers who had been exposed to the brand’s social media promotions. A total of 150 respondents were selected using purposive sampling. Data were analysed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method through SmartPLS.Results: The findings reveal that Social Media Marketing has a positive and significant effect on Purchase Intention. Brand Image also shows a positive and significant influence on Purchase Intention. However, Purchase Intention does not significantly affect Purchase Decisions. Similarly, the indirect effects of Social Media Marketing and Brand Image on Purchase Decisions through Purchase Intention were found to be insignificant.Applications/Originality/Value: This study provides empirical evidence on the effectiveness of digital marketing strategies for micro businesses, particularly in the culinary sector. The findings highlight the importance of strengthening brand image and optimising social media content to enhance consumer engagement.